Cold snare piecemeal resection of colonic and duodenal polyps ≥1 cm - Choksi, Neel; Elmunzer, B. Joseph; Stidham, Ryan W.; Shuster, Dmitry; Piraka, Cyrus (Endoscopy International Open, 2015)
Background: Endoscopic removal of duodenal and colorectal adenomas is currently considered to be the standard of care for prevention of adenocarcinoma. The use of cautery carries a risk of delayed bleeding, post-polypectomy syndrome, and perforation. We examined the safety and feasibility of removing colonic and duodenal polyps ≥ 1 cm using a piecemeal cold snare polypectomy technique.Patients: The study included 15 patients with duodenal polyps ≥ 1 cm and 15 patients with colonic polyps ≥ 1 cm.Main outcome measurements: Bleeding, perforation, abdominal pain, or hospitalization occurring within 2 weeks of polypectomy.Results: Between 24 August 2011 and 29 April 2013, 15 patients had removal of duodenal polyps ≥ 1 cm. Mean patient age was 64 years and 9/15 patients were male. The mean polyp size was 24 mm (10 – 60 mm). All polyps were removed with a cold snare and some required cold biopsy forceps. One patient required hospitalization for gastrointestinal blood loss 7 days post-polypectomy; this patient was using Coumadin. Between 27 February 2012 and 30 May 2013, 15 patients underwent resection of a ≥ 1 cm colonic polyp. Mean patient age was 68 years and 9/15 were male. The mean polyp size was 20 mm (10 – 45 mm). All polyps were primarily removed with a cold snare. None of the patients required hemostatic clips for control of immediate bleeding. One patient presented to the emergency department with abdominal pain 1 day after initial endoscopy. CT scan showed no abnormalities and the patient was discharged.Conclusions: Cold snare polypectomy for large duodenal and colonic polyps is technically feasible and may have a favorable safety profile compared to standard electrocautery-based endoscopic resection. Comparative trials are required to determine the relative safety and efficacy of cold snare techniques for complete and durable resection of large polyps compared to standard hot snare methods.